Critical discourse analysis (CDA) of the 16th Venice Architecture Biennale manifesto - Topaloğlu, Gürkan; Beşgen, Asu (Journal of Architecture and Urbanism, 2023)
The Venice Architecture Biennale emerged with post-modern thought in the late 1970s and early 1980s. It is a medium where political, economic and cultural transformations are experienced in the field of architecture and where mainstream global architecture is discussed and shared. Over time, the Venice Architecture Biennale has created a global focal point with the manifestos produced, while bringing together the architectural products and ideas in the ambiguity of the boundaries of local architecture. Biennial manifestos have an ideological structure that is oriented towards social relations in the field of architecture. Looking at the recent Venice Architecture Biennale, it can be said that knowledge production is at the forefront in discourses and products which develops critical thinking. In this context, the study deals with the manifesto1 of the 16th Venice Architecture Biennale. The 2018’s manifesto which was produced within the scope of the biennial; the curator’s ideology is worth examining because of its subjective and objective judgments. For this reason, Norman Fairclough’s critical discourse analysis (CDA) was used in the study to make a critical reading of the biennial manifestos. By using the characteristics of CDA, findings and conclusions were reached in the topics of ideology, interpretation and consistency of the discourse. Due to the nature of the analysis, the findings and conclusions have revealed a new discourse that is controversial in this field.